A Multimodal Approach to Teach Novice Researchers How to Deal with Discussion Sessions in Conference Paper Presentations - Querol-Julián, Mercedes (6TH International Conference of Education, Research and Innovation (ICERI 2013), 2020)
The nature of spoken academic English is a complex construct if compared with its written counterparts, for example delivering a conference paper presentation and publishing an article in a journal. However, both are genres that post-graduate students need to master to disseminate their research and try to find a position in the scientific community. However, traditionally discourse analysis of both academic genres, and its final pedagogical aim, has focused exclusively on teaching the macro and microstructure on the grounds of only the linguistics aspects. That is, a spoken research academic genre such as conference paper presentations has in general been studied, first, and taught latter, from the analysis of corpora of verbatim transcriptions. The study presents an approach to teach the discourse of conference paper presentations, and particularly of the discussion sessions that follow them, that based on a multimodal perspective which takes into account the whole picture, where linguistic and non-linguistic (kinesics and paralanguage) aspects are considered. This methodology is rooted on previous research on genre analysis (Swales 1990), systemic functional linguistics (Halliday 1985), conversation analysis (Schegloff & Sacks 1973), multimodal discourse analysis (Kress & van Leeuwen 2001), and pragmatics (Brown & Levison 1978, 1987). This theoretical framework helps to understand the complexity of the interaction in discussion sessions and allows the teacher to present full examples of the spoken discourse using ELAN (EUDICO Linguistic Annotator), a multimodal annotation tool. The teacher can bring to the class the different moves found in the discussion, e.g. in an exchange where the discussant's comment is followed but a presenter's comment, the teacher can illustrate linguistic expressions of the discussant's opening turn, contextualizing comment, making comment (criticizing research or showing alignment with the presenter); and the presenter's opening turn, replying to comment (rejecting or, rejecting and then acknowledging, or acknowledging and then rejecting) and rationalizing position; with the non-linguistic expression, showing how it is actually said since the video and audio recordings are also available to the students in a synchronized way. This methodology allows the teachers to prepare their own materials to support with real examples those aspects that are of special interest for their students. Besides post-graduate students will have the opportunity to see real examples of how to act and interact during the discussion sessions for different purposes. It is important to notice the difficulty that discussions involves, since whereas the presentation of the research can be prepared in advanced, even rehearsed, in the discussion, novice researchers move to an unprepared discourse where they do not know the directions it can take.
Keywords: discussion sessions; multimodal approach; post-graduate students; WOS(2)